Talking with My Daughter About Archives: Métis Researchers and Genealogy - Loyer, Jessie; Loyer, Darrell (KULA, 2021)
In a kitchen table discussion, a Métis genealogist and his Cree-Métis librarian daughter talk about the ways Indigenous people navigate archives, oral history, and research; discuss the inaccuracies that exist in records relating to Indigenous people; and consider the ways that records can supplement oral history about Métis culture.